Incidentally Detected Cardiac and Hepatic Hydatid Cyst after Sudden Onset Facial Paralysis: A Case Report - Stiru, Ovidiu; Geana, Roxana Carmen; Antohi, Laura; David, Leonard; Goicea, Mihai; Paunescu, Alina; Chioncel, Ovidiu; Iliescu, Vlad Anton (Archives of Clinical and Medical Case Reports, 2019)
The simultaneous occurrence of interventricular cardiac septum and hepatic localization for cystic echinococcosis is a very rare form of presentation and it may lead to various complications. We present the case of a 24-year-old man who was admitted to the hospital for evaluation of abrupt onset facial paralysis and incidentally diagnosed with a large hepatic hydatid cyst and a cardiac one located in the interventricular septum. The patient did not have any other symptoms associated with hydatid disease before this event. In this case, we surgically removed both hydatid cysts at the same time, to prevent complications and to establish a better outcome for the patient.